'Hot cities' and rapid growth; experiences and responses of urban planning departments. Issue 3 (7th August 2022) - Hammarberg, Robert; Highfield, Linda; Walton, Gretchen; Wermuth, Paige; Bowman, Ann
Abstract: It is presumed that rapidly growing 'hot cities' adapt their planning and operations to meet their evolving population's needs. These presumptions inspired the development of the following mixed‐method, convergent parallel study. Data from urban planning officials across nine rapidly growing 'hot cities' were collected through pre‐interview surveys and qualitative key‐informant interviews. Thematic analysis was used to identify salient issues regarding awareness and perception of rapid population growth and the resulting response from their departments. Results indicate two main themes; Multidimensional Strain and Mitigation Strategies describe city experiences with rapid population growth effects and response. Across cities, urban planners expressed similar experiences of stress on land usage, housing, transportation, programing, and service delivery. Similar response patterns included evaluation and innovation of growth management strategies, enhanced collaboration, and equity considerations. This snapshot of rapid population growth repercussions and current city mitigation strategies may have future implications for public health and urban planning administrators in practice. Results shared also indicate how population data use and sharing can support Mitigation Strategies and impact community health.